Dampak Sosial Dan Lingkungan : Inovasi Kewirausahaan Lembaga Pondok Pesantren Ekologi Ath Thaariq - robaiyadi .; Cecep Castrawijaya (GLOBAL SCIENTS PUBLISHER, 2025)
Islamic boarding schools, as Islamic educational institutions, have great potential to become driving forces for social and environmental change through innovative entrepreneurial activities. Objective: This study aims to describe the entrepreneurial innovation model developed by the Ath-Thaariq Ecological Islamic Boarding School and its resulting social and environmental impacts. The research method uses a literature review research approach (systematic literature review). Results: The study shows that entrepreneurship at the Ath-Thaariq Ecological Islamic Boarding School is not only oriented towards economic profit, but also towards community empowerment and environmental preservation.Innovation based on agroecology, organic farming, and student entrepreneurship training are concrete practices of da'wah bil hal (Islamic outreach) that reflect the Islamic value of rahmatan lil 'alamin.